2018
DOI: 10.1038/s41467-018-06378-9
|View full text |Cite
|
Sign up to set email alerts
|

One-step generation of multiple gene knock-outs in the diatom Phaeodactylum tricornutum by DNA-free genome editing

Abstract: Recently developed transgenic techniques to explore and exploit the metabolic potential of microalgae present several drawbacks associated with the delivery of exogenous DNA into the cells and its subsequent integration at random sites within the genome. Here, we report a highly efficient multiplex genome-editing method in the diatom Phaeodactylum tricornutum, relying on the biolistic delivery of CRISPR-Cas9 ribonucleoproteins coupled with the identification of two endogenous counter-selectable markers, PtUMPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 32 publications
4
121
0
Order By: Relevance
“…Additionally, the knockouts survived on 5-FOA concentrations that fully inhibited the growth of wild-type P. tricornutum ( Figure 4A). This is consistent with phenotypes previously observed for P. tricornutum UMPS knockouts 7,21 . There was a slight growth advantage of ∆UMPS1 over ∆UMPS2 on media supplemented with both 5-FOA and uracil, but not on media containing uracil alone.…”
Section: Phenotypic and Metabolomic Characterization The Ptumps Knocksupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the knockouts survived on 5-FOA concentrations that fully inhibited the growth of wild-type P. tricornutum ( Figure 4A). This is consistent with phenotypes previously observed for P. tricornutum UMPS knockouts 7,21 . There was a slight growth advantage of ∆UMPS1 over ∆UMPS2 on media supplemented with both 5-FOA and uracil, but not on media containing uracil alone.…”
Section: Phenotypic and Metabolomic Characterization The Ptumps Knocksupporting
confidence: 92%
“…The available tools for genetic manipulation of P. tricornutum have grown substantially in recent years, including the adaptation of TALEN and Cas9 genome-editing nucleases for targeted knockouts [6][7][8][9]30 . Examination of edited sites in P. tricornutum and other organisms has revealed that many Cas9 events are not homogeneous.…”
Section: Implications For Expanding the P Tricornutum Genetic Toolboxmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent breakthrough was the development of genome editing through Zn-Finger Nucleases, Transcription Activator-Like Effector Nucleases (TALENs), and CRISPR/Cas9 for different eukaryotic algae. TALENs were successfully used for P. tricornutum (Weyman et al, 2015;Serif et al, 2018), whereas Znfinger nucleases were developed for Chlamydomonas (Sizova et al, 2013;Greiner et al, 2017). CRISPR/Cas9 genome editing was achieved in Chlamydomonas (Shin et al, 2016;Greiner et al, 2017), P. tricornutum (Nymark et al, 2016;Serif et al, 2018;Slattery et al, 2018), and T. pseudonana (Hopes et al, 2016).…”
Section: Genome Editing Toolsmentioning
confidence: 99%
“…The eukaryotic microalga Phaeodactylum tricornutum is considered an attractive candidate for the production of a wide range commodity components (Kikutani et al, ; Xue et al, ). With the availability of sequenced genome and genetic toolkit, P. tricornutum has garnered huge research attention for metabolic engineering (Niu et al, ; Serif et al, ). Harnessing lipid metabolic pathways in oleaginous microalgae hold great potential for scalable biofuel production (Xue et al, ).…”
Section: Introductionmentioning
confidence: 99%